Expression, offence and censorship : the sexually provocative image and the representation of female sexuality in South African art - Lynch, Tracy(Tracy Lee) (Stellenbosch : Stellenbosch University, 2012)
Study project (M.A.) -- University of Stellenbosch, 1997.